Use of functional magnetic resonance imaging to assess cognition and consciousness in severe Guillain-Barré syndrome - Norton, L; Graham, M; Kazazian, K; Gofton, T; Weijer, C; Debicki, D; Fernandez-Espejo, D; Thenayan, EA; Owen, AM (Elsevier, 2022)
Objective: Functional neuroimaging may provide a viable means of assessment and communication in patients with Guillain-Barré Syndrome (GBS) mimicking the complete locked-in state. Functional neuroimaging has been used to assess residual cognitive function and has allowed for binary communication with other behaviourally non-responsive patients, such as those diagnosed with unresponsive wakefulness syndrome. We evaluated the potential application of functional neuroimaging using a clinical-grade scanner to determine if individuals with severe GBS retained auditory function, command following, and communication. Methods: Fourteen healthy participants and two GBS patients were asked to perform motor imagery and spatial navigation imagery tasks while being scanned using functional magnetic resonance imaging. The GBS patients were also asked to perform additional functional neuroimaging scans to attempt communication. Results: The motor imagery and spatial navigation task elicited significant activation in appropriate regions of interest for both GBS patients, indicating intact command following. Both patients were able to use the imagery technique to communicate in some instances. Patient 1 was able to use one of four communication tasks to answer a question correctly. Patient 2 was able to use three of seven communication tasks. However, two questions were incorrectly answered while a third was non-verifiable. Conclusions: GBS patients can respond using mental imagery and these responses can be detected using functional neuroimaging. Furthermore, these patients may also be able to use mental imagery to provide answers to ‘yes’ or ‘no’ questions in some instances. We argue that the most appropriate use of neuroimaging-based communication in these patients is to allow them to communicate wishes or preferences and assent to previously expressed decisions, rather than to facilitate decision-making.